A responsabilidade dos sócios e demais pessoas físicas na sociedade limitada perante os débitos relativos ao custeio da previdência social - Camozzi, Érika (2007)
The present study has as its objective to analyze the responsibility limitation of the partners, the managers and the administrators for the company liabilities of the private limited companies regarding the Social Security. It will be analyzed the debtor of the tax liability, its concept and choosing way, differentiating taxpayers and responsible persons for the Social Security credit, against the company, within the aspects as outlined by the National Tax Code. The personality of the corporate body will be analyzed in order to point out its main attribution: the patrimonial autonomy, an attribution that is of the essence for the correct ascribing of responsibility to the individuals regarding the fiscal debts as assumed. The autonomy of the corporate body is of utmost importance for the economic development as it limits the investor s responsibility. Consequently, the theme of the partners responsibility will also be approached, under an economic prism, through the analysis of the relationship between the limitation of the partners responsibility and the economic efficiency, taking into account the fact that the rule, that establishes the partners limited responsibility for the company liabilities, is focused on enhancing and fomenting the economic activities, becoming an instrument that results from the capitalist structure. The controversy of the subject matter is shown very clearly when we take a quick look at the scenery of the status of companies in the country, being pressed by a growing increase in the taxation burden and by the successive economic plans that do not promote, be directly or indirectly, the development of the economy. It is not without a reason that there is tax default, being presently shown, in the massive majority of cases, the impossibility by the corporate bodies to cover the existing debts with their assets, giving an opportunity to the Tax Bureau to involve the partners and other individuals in the tax foreclosures, having a purpose more intimidating than efficacious. The theory of the corporate entity disregard will be approached with the objective of outlining criteria for its correct application, considering that the Article 50 of the 2002 Civil Code was an advance in order to guide the correct application of the theory as it brought the necessary effectiveness to the Law professionals. The concern, that was pointed out by the doctrine on an on-going basis, was how the theory of the corporate entity disregard has been utilized by our Courts, in order that it is not indiscriminately applied, being kept the principle of the corporate body autonomy, to be disregarded only in exceptional cases. The issue of the responsibility of the partners and other individuals rotates around the Article 135, item III of the National Tax Code. In accordance with such provision, the administrators of limited companies become personally liable for the fiscal debts of the company as from the time they start taking action with excessive powers or with violation to the law. It will be analyzed the hypothesis in which the partner is liable for obligations that, in theory, should belong to the company, that is, 10 the hypothesis as established on the Article 13 of the Law 8,212/93. Therefore, it is necessary the joint analysis of the Articles 124, 128 and 135 of the National Tax Code with the Article 13 of the Law 8,212/91. It will still be approached the question of the unconstitutionality of this specific Article 13 which, due to the fact of legislating as regards to general rules of Tax Law, violates what is established by our Constitution, on Article 146, item III, subitem b , requiring a complementary law to the Constitution in order to legislate about the matter. And, finally, at a practical level, it will be analyzed the question related to the necessary inclusion of the name of partners, managers and administrators on the executive document of the Tax Bureau, under penalty of nullity of the registration and consequent collection action